Drilorhinus, a new genus of the family Drilidae Lacordaire, 1857 (Coleoptera: Elateroidea) from Iran - Kovalev, Alexey V.; Kirejtshuk, Alexander G.; Shapovalov, Andrey M. (Zootaxa, 2019)
A new genus of the family Drilidae, Drilorhinus gen. nov. with one new species D. klimenkoi sp. nov. from the South-West Iran (Lorestan) is described, illustrated and compared with all known genera of this group. The new genus differs from all members of the family in the strong projection of the anterior part of the frons between antennal insertions. Some problems of taxonomic rank and classification of Drilidae are considered.